Synaptic and functional alterations in the development of mutant huntingtin expressing hiPSC‐derived neurons - Dinamarca, Margarita C.; Colombo, Laura; Tousiaki, Natalia E.; Müller, Matthias; Pecho-Vrieseling, Eline (Frontiers in Molecular Biosciences, 2022)
Huntington disease (HD) is a monogenic disease that results in a combination of motor, psychiatric and cognitive symptoms. It is caused by a CAG trinucleotide repeat expansion in the exon 1 of the huntingtin (HTT) gene, which results in the production of a mutant HTT protein (mhtt) with and extended polyglutamine tract (PolyQ). Severe motor symptoms are a hallmark of HD and typically appear during middle age; however, mild cognitive and personality changes often occur already during early adolescent. Wild-type htt is a regulator of synaptic function and plays a role in axon guidance, neurotransmitter release and synaptic vesicle trafficking. These functions are important for proper synapse assembly during neuronal network formation. In the present study we assessed the effect of mhtt exon1 isoform on the synaptic and functional maturation of human-induced pluripotent stem cell (hiPSC)-derived neurons. We used here a relative fast maturing hiPSC line carrying a doxycycline-inducible pro-neuronal transcription factor, Ngn2 (iNgn2), and generated a double transgenic line by introducing only the exon 1 of HTT, which carries the mutant CAG (mhttEx1). The characterization of our cell lines revealed that the presence of mhttEx1 in hiPSC-derived neurons alters synaptic protein appearance, decreases synaptic contacts and causes a delay in the development of a mature neuronal activity pattern, recapitulating some of the developmental alterations observed in HD models, nonetheless in a shorted time window. Our data supports the notion that HD has a neurodevelopmental component and is not solely a degenerative disease.